2003
DOI: 10.1103/physrevb.67.245203
|View full text |Cite
|
Sign up to set email alerts
|

Theory of excited-state absorption in phenylene-basedπ-conjugated polymers

Abstract: Within a rigid-band correlated electron model for oligomers of poly-͑paraphenylene͒ ͑PPP͒ and poly͑paraphenylenevinylene͒ ͑PPV͒, we show that there exist two fundamentally different classes of two-photon A g states in these systems to which photoinduced absorption ͑PA͒ can occur. At relatively lower energies there occur A g states which are superpositions of one electron-one hole (1e -1h) and two electron-two hole (2e -2h) excitations, that are both comprised of the highest delocalized valence-band and the low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 60 publications
4
39
1
Order By: Relevance
“…In a recent theoretical analysis of the 1B u PA spectra of PPV, which also has two prominent bands labeled PA1 and PA2, we indeed found that the first and the most intense peak ͑PA1͒ contributing to the spectra was indeed the mA g state of the polymer. 21 …”
Section: A Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent theoretical analysis of the 1B u PA spectra of PPV, which also has two prominent bands labeled PA1 and PA2, we indeed found that the first and the most intense peak ͑PA1͒ contributing to the spectra was indeed the mA g state of the polymer. 21 …”
Section: A Experimental Resultsmentioning
confidence: 99%
“…Comparing these states to the ones contributing resonant peaks to the TPA and THG spectra of oligo-PDPA's calculated by us earlier, 16,17 we conclude that these states correspond to nothing but the mA g states of the corresponding oligo-PDPA. Recalling that the mA g is the state with a very strong dipole coupling to the 1B u state, which makes its presence prominent in both the TPA and THG spectra of several conjugated polymers, 13,21 it should not at all be surprising that it leads to an intense peak in their 1B u PA spectra as well. Indeed, in a recent calculation performed on oligomers of PPP and PPV, 21 we identified the first feature of their 1B u PA spectra with their mA g states.…”
Section: B U Pa Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, our group and collaborators(author?) [28,29,30,31,32,33,34,35,36,37,38,39,40], along with numerous other groups(author?) [1,2,3,41,42,43,44,45,46], have used the P-P-P model to study the electronic structure and optical properties of conjugated molecules and oligomers.…”
Section: Introductionmentioning
confidence: 99%